Rapid inhalational induction of anaesthesia-with special reference to the use of isoflurane - Van Heerden, Peter, Vernon (My University, 1991)
Recognising that halothane is declining as the volatile anaesthetic agent of choice for inhalational induction and that isoflurane is replacing it, particularly in North America and Europe, this study was designed to determine whether isoflurane is comparable to halothane with respect to speed of induction and complication rate when used for rapid inhalational induction (RII) of anaesthesia.
A research University fulfillment Medicine (in report submitted to the Faculty of Medicine, of the Witwatersrand, Johannesburg, in partial of the requirements for the degree of Master of the branch of Anaesthesia
Keywords: Anesthesia; Isoflurane; Halothane